PP1 Identifying genetic risk factors for ACL rupture and/or Achilles tendinopathy in Newcastle United FC players. (21st October 2014) - Catterson, P; Trueman, L
Abstract : ACL rupture and Achilles tendinopathy are common and problematic sports related injuries, with research surrounding genetic predisposition to them limited but producing a growing body of evidence. The aim of this study was to determine whether NUFC players have genetic predisposition to these injuries and compare the results to retrospective injury data. DNA from buccal cells was collected via cheek swab after informed consent, and samples were tested for genotypes of biomarkers that are thought to predispose to ACL rupture (COL12A1 (Posthumus et al., BJSM . 2010 Dec; 44 (16):1160–5)) and Achilles tendinopathy (MMP3 (Collins and Raleigh, Med Sport Sci. 2009; 54 :136–49) and GDF5 (Posthumus et al., Rheum . 2010; 49 :2090–97). If a biomarker's genotype was "at risk" (predisposed to injury) the players were placed in the relevant injury risk group. Retrospective injury data was then compared. 27 players (mean = 24.7 y, range = 15 y) were tested, with three players returning no "at risk" results (and no corresponding injuries). Of those "at risk"; 7 players were at risk from both ACL rupture and Achilles tendinopathy (with 1 corresponding injury in this group), 9 players were at risk from Achilles tendinopathy alone (with 1 corresponding injury in this group) and 8 players were at risk from ACL rupture alone (with 3 corresponding injuries in this group). Therefore, a large proportion (90%) of the NUFC players tested have genetic predisposition to these injuries. The comparison with retrospective injury data also supports previous hypotheses, as all retrospective ACL ruptures and Achilles tendinopathies corresponded with their injury risk groups. Research in larger groups is required in the future to further test this claim.